PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Siti A. M. Karubaba; Bobbi Rahman; Samsul Arifin (IndoMath: Indonesia Mathematics Education, 2019)
This study aims to investigate whether the ability to understand mathematical concepts of students who get cooperative learning think pair square type is higher than students who get conventional learning. The research method used is a quasi-experimental method with a research design that is nonequivalent control group design. In this study sample selection using the Convenience Sampling technique is students of class VIII.5 as the control class and students of class VIII.6 as the experimental class. Experimental class students get learning using the think pair square learning model, while students in the control class get conventional learning. The instruments in this study were in the form of pretest and posttest questions in the form of questions describing the ability to understand students' mathematical concepts. In the research that has been done, the significance (sig.) 0,000 is smaller than the significance level Î± = 0.05. The research hypothesis testing was carried out by the Mann-Whitney test using SPSS and a significance level of 5% (Î± = 0.05).. In this study it was found that the ability to understand mathematical concepts of students who received think pair square learning was higher than students who obtained conventional learning.